Ninho de nós: sentidos da atividade humana em terapia ocupacional - Cardinalli, Isadora (Universidade Federal de São Carlos, 2022)
The terminological issue involves several dimensions, forces and interests, but the conceptual elaboration is at the center of the philosophical and scientific debate. The statement human activity was strengthened in the discourses of Brazilian occupational therapy after the questioning of contradictions in its practices, whose meaning was being instrumentalized for domination by power structures. The refusal to imperialism and the reproduction of decontextualized models appeared among the first national publications, which established dialogues with other fields of knowledge and critical perspectives, which supported the human and cultural significance for activity in occupational therapy. This research was dedicated to the discourses, events and conditions surrounding the emergence and support of the statement human activity and its understandings along with the productions of Brazilian occupational therapists; as well as promoting experiences and producing meanings about human activity. The archeology of knowledge and the genealogy of power supported the excavation of the statement and the implication of forces related to language, culture, socio-historical-political construction, economic and scientific influence. Academic and professional discourses were excavated in three layers: literature review (60 articles), virtual questionnaire (81 participations) and experience narrative letters (14 participations). The intervention research was based on clues from the cartography method to promote relationships between experience, life and knowledge production, revealing three investments: words, experiences and the creation of meanings. The conceptual analysis reveals graduations and various elements for understanding the utterance: from a technical notion to understandings based on the expression of life. The narratives show that the unique elaboration of the experience, involved in the encounter and in doing together, recognizes references and inspirations, as well as producing recreations and an authorial know-how. The discourses show impacts of the perception of domination and violence in the Brazilian cultural construction, but also reveal hopeful initiatives for the transformation of conditions, which marks a production of difference in Brazilian occupational therapy; philosophy and arts are highlighted, in addition to science, contributing to the elaboration of knowledge from experience, which adds complex meanings to human activity in occupational therapy. The discussion of what was produced by the intervention research involves an ethical-aesthetic-political consideration of language and a construction of knowledge from experience in the sense of making-knowing. The reflection on the meaning of human activity intrinsically related to the production of life and knowledge is affirmed, contributing to the construction of an occupational therapy that welcomes experiences and promotes self-care and the production of the common world.
Nest of us/knots: meanings of human activity in occupational therapy
Keywords: Terapia ocupacional; Atividades humanas; Epistemologia; Terminologia; Narrativa pessoal; Occupational therapy; Human activities; Epistemology; Terminology; Personal narrative; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL